A fast and highly sensitive blood culture PCR method for clinical detection of Salmonella enterica serovar Typhi - Zhou Liqing; Pollard Andrew J (BMC, 2010)
Abstract Background Salmonella Typhi causes an estimated 21 million new cases of typhoid fever and 216,000 deaths every year. Blood culture is currently the gold standard for diagnosis of typhoid fever, but it is time-consuming and takes several days for isolation and identification of causative organisms. It is then too late to initiate proper antibiotic therapy. Serological tests have very low sensitivity and specificity, and no practical value in endemic areas. As early diagnosis of the disease and prompt treatment are essential for optimal management, especially in children, a rapid sensitive detection method for typhoid fever is urgently needed. Although PCR is sensitive and rapid, initial research indicated similar sensitivity to blood culture and lower specificity. We developed a fast and highly sensitive blood culture PCR method for detection of Salmonella Typhi, allowing same-day initiation of treatment after accurate diagnosis of typhoid. Methods An ox bile tryptone soy broth was optimized for blood culture, which allows the complete lysis of blood cells to release intracellular bacteria without inhibiting the growth of Salmonella Typhi. Using the optimised broth Salmonella Typhi bacteria in artificial blood samples were enriched in blood culture and then detected by a PCR targeting the fliC-d gene of Salmonella Typhi. Results Tests demonstrated that 2.4% ox bile in blood culture not only lyzes blood cells completely within 1.5 hours so that the intracellular bacteria could be released, but also has no inhibiting effect on the growth of Salmonella Typhi. Three hour enrichment of Salmonella Typhi in tryptone soya broth containing 2.4% ox bile could increase the bacterial number from 0.75 CFU per millilitre of blood which is similar to clinical typhoid samples to the level which regular PCR can detect. The whole blood culture PCR assay takes less than 8 hours to complete rather than several days for conventional blood culture. Conclusions This novel blood culture PCR method is superior in speed and sensitivity to both conventional blood culture and PCR assays. Its use in clinical diagnosis may allow early detection of the causative organism and facilitate initiation of prompt treatment among patients with typhoid fever.